﻿Evaluation of soil genotoxicity in Karvachar and Kapan using the comet assay in ural field mouse (Apodemus uralensis) - A. E. Simonyan (ՀՀ ԳԱԱ հրատ.)
﻿The aim of the present study was evaluation of soil genotoxicity from Karvachar (Nagorno-Karabakh Republic) and Kapan (Republic of Armenia) using the single cell gel electrophoresis (comet assay) on peripheral blood leukocytes of the local Ural field mouse (Apodemus uralensis). DNA damage in mice leukocytes from Karvachar was significantly higher compared to Kapan. It is worth to mention, that in the soil samples from Karvachar the content of Fe, Mg and Ca was significantly higher compared to Kapan indicating potential genotoxic influence. The obtained results confirm that the assessing of genotoxicity by the Comet assay in free-living mice is valuable test in monoitoring of environmental pollution. ﻿Աշխատանքի նպատակն էր Քարվաճառի (Լեռնային Ղարաբաղի Հանրապետություն) և Կապանի (Հայաստանի Հանրապետություն) հողի գենաթունայնության գնահատումը փոքր անտառային մկան (Apodemus uralensis) ծայրամասային արյան լեյկոցիտներում եզակի բջիջների ժել-էլեկտրաֆորեզի (ԴՆԹ-կոմետ մեթոդ) կիրառմամբ: Քարվաճառի անտառային մկների լեյկոցիտներում ԴՆԹ-ի վնասվածքները հավաստիորեն ավելի բարձր են, համեմատած Կապանի մկների հետ: Հարկ է նշել, որ Քարվաճառի հողի նմուշներում Fe, Mg և Ca պարունակությունը զգալիորեն ավելի բարձր է, համեմատած Կապանի հետ, ինչը վկայում է հնարավոր գենաթունային ազդեցության մասին: ԴՆԹ-կոմետ մեթոդի կիրառումը փոքր անտառային մկան ծայրամասային արյան լեյկոցիտներում արդյունավետ մոտեցում է հողի գենաթունայնության գնահատման համար: ﻿Целью настоящего исследования являлась оценка генотоксичности почв Карвачара (Нагорно-Карабахская Республика) и Капана (Республика Армения), с применением метода гель-электрофореза единичных клеток (метод ДНК-комет) в лейкоцитах периферической крови у малой лесной мыши (Apodemus uralensis). Уровни повреждений ДНК в лейкоцитах мышей из Карвачара были значительно выше по сравнению с мышами из Капана. Стоит отметить, что в пробах почвы из Карвачара содержание Fe, Mg и Са было значительно выше по сравнению с образцами почв из Капана, что указывает на потенциальное генотоксическое влияние. Полученные результаты подтверждают, что оценка генотоксичности почв с применением метода ДНК-комет у малой лесной мыши является эффективным подходом для мониторинга окружающей среды.
Keywords: Biology; Molecular Biology; Botany